Pengaruh Infusa Batang Pisang Kepok Kuning terhadap Daya Hambat Pertumbuhan Bakteri Escherichia Coli secara In Vitro - Dewi Suryani Ningsih; Lamri; Abdul Holik Subaeri (Jurnal Sains & Kesehatan, 2023)
Diarrheal disease is one of the main causes of morbidity and death worldwide. Diarrheal disease is an infection caused by pathogenic bacteriaEscherichia Coli. Kepok banana stems have antibacterial properties that can inhibit bacterial growthE. coli. The purpose of this study was to determine the diameter of the inhibition zone on bacterial growthE. coli. This study used the infusion method by taking the kepok banana stem as the research sample. The inhibition of kepok banana stem infusion was tested by the methodKirby Bauer diffusion using disc paper. This study used kepok banana stem infusion with various concentrations. The concentration used starts from 60%, 70%, 80%, 90% and 100% with 4 repetitions. The positive control used chloramphenicol and distilled water as negative controls. This research is included in the type of researchTrue experimentalby design Posttest-Only With Control group Design. The results in this study stated that no inhibition zone was formed against bacterial growthEscherichia coli.These results are shown by the results of measuring the diameter of inhibition after 24 hours of incubation which is 0 mm and chloramphenicol as a positive control has an average inhibition of 27.6 mm and it is stated that chloramphenicol is sensitive to bacteria E.Coli. This can be caused by the small content of antibacterial substances that can dissolve in aquadest (infusion method). The conclusion is that the infusion of kepok banana stems does not have the effectiveness of inhibiting the growth of bacteria Escherichia Coli.Suggestions for future researchers to conduct this research using samples from other parts of the banana tree and can also use a different extraction method.